2005
DOI: 10.1121/1.1886387
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the feasibility of acoustical tweezers: Ray acoustics approach

Abstract: The optical tweezer has been found to have many biomedical applications in trapping macromolecules and cells. For the trapping mechanism, there has to be a sharp spatial change in axial optical intensity and the particle size must be much greater than the wavelength. Similar phenomenon may exist in acoustics. This work was undertaken to demonstrate theoretically that it is possible to acoustically trap particles near the focal point where most of the acoustic energy is concentrated if certain conditions are me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
75
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 18 publications
3
75
0
Order By: Relevance
“…Initially, these 'acoustical tweezers' used opposing focused transducers to produce a trap at their, common, focal point (Wu 1991). More recent theoretical (Lee et al 2005;Lee & Shung 2006) and experimental (Lee et al 2009) work has demonstrated the feasibility of using a single focused transducer working at a high frequency (30 MHz) to trap particles much larger than a wavelength in diameter against a surface. Particle manipulation has been achieved by moving the transducer and hence the focal position.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, these 'acoustical tweezers' used opposing focused transducers to produce a trap at their, common, focal point (Wu 1991). More recent theoretical (Lee et al 2005;Lee & Shung 2006) and experimental (Lee et al 2009) work has demonstrated the feasibility of using a single focused transducer working at a high frequency (30 MHz) to trap particles much larger than a wavelength in diameter against a surface. Particle manipulation has been achieved by moving the transducer and hence the focal position.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of acoustic radiation force on rigid and elastic spherical/cylindrical particles in an unfocused sound field has been the subject of many studies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The very first studies on acoustic radiation force are those by King [8], Embleton [21], Gor'kov [22] and Nyborg [23], in which, several theoretical models for the calculation of the radiation force on spherical particles in different acoustical fields had been developed [24].…”
Section: Introductionmentioning
confidence: 99%
“…While the experimental activities have been mainly concerned with the application of standing waves and Gaussian beams [1][2][3][4][5][6][7], a better understanding of the nature of the problem has been gained through the development of a number of mathematical models using King's derivation of the exerted radiation force and the standard wave decomposition method [8][9][10][11][12][13][14][15][16][17][18][19]. The problem of acoustic radiation force for Gaussian beams, on the other hand, has often been dealt with using ray acoustics method; see for example [20]. In the next paragraphs, we shall provide a review of these two methods and the application of Gaussian beams for acoustic manipulation of fine particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a focused needle ultrasonic transducer offers more flexibility in carrying out single beam acoustic trapping experiments given the extremely congested environment in the small area within which the experiments are performed. 4 For a miniaturized transducer, piezoelectric materials with high dielectric constant are more desirable since the electrical impedance of a transducer is inversely proportional to the dielectric constant of the piezoelectric material. 5 Comparing with other materials, Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PMN-PT) single crystal is a promising candidate to build small transducers because of its high dielectric constant (1000-5000).…”
mentioning
confidence: 99%